Studies on partial and total photon interaction parameters in the energy range 1 keV–100 GeV of some synthetic polymers having medical applications. (March 2021) - Thulasi, P.V.; Joseph, Antony; Varier, K.M.
Abstract: The effective atomic numbers and effective electron densities of some polymers having medical applications are determined for total as well as partial gamma ray interaction processes in the wide range of energies 1 keV to 100 GeV. Mass energy-absorption coefficient and effective atomic number corresponding to gamma ray energy absorption in these media are also estimated for the energy range of 1 keV–20 MeV. These parameters are found to vary with energy and chemical composition of the polymers. These variations are shown graphically and are discussed in detail. The estimated values are compared with experimental data, wherever available, and these show good agreement. The kerma relative to air of these polymers are also calculated for 1 keV-20 MeV. Kerma remains constant at unity from 200 keV to 10 MeV. The selected polymers have remarkable applications in the medical field and we expect that the data will be useful in medical domain. Highlights: Photon interaction response of eleven polymers is explored for energy 1 keV-100 GeV. Mass energy-absorption coefficient and kerma of these were evaluated. Their effective atomic number and electron density values were also extracted. Variation with energy of these parameters studied for total and partial interactions. Comparison with available experimental data shows good agreement.